Reactive uptake of NO2 on volcanic particles: A possible source of HONO in the atmosphere - Romanias, Manolis N; Ren, Yangang; Grosselin, Benoit; Daële, Véronique; Mellouki, Abdelwahid; Dagsson-Waldhauserova, Pavla; Thevenet, Frederic (Journal of environmental sciences (China), 2020)
The heterogeneous degradation of nitrogen dioxide (NO2) on five samples of natural Icelandic volcanic particles has been investigated. Laboratory experiments were carried out under simulated atmospheric conditions using a coated wall flow tube (CWFT). The CWFT reactor was coupled to a blue light nitrogen oxides analyzer (NOx analyzer), and a long path absorption photometer (LOPAP) to monitor in real time the concentrations of NO2, NO and HONO, respectively. Under dark and ambient relative humidity conditions, the steady state uptake coefficients of NO2 varied significantly between the volcanic samples probably due to differences in magma composition and morphological variation related with the density of surface OH groups. The irradiation of the surface with simulated sunlight enhanced the uptake coefficients by a factor of three indicating that photo-induced processes on the surface of the dust occur. Furthermore, the product yields of NO and HONO were determined under both dark and simulated sunlight conditions. The relative humidity was found to influence the distribution of gaseous products, promoting the formation of gaseous HONO. A detailed reaction mechanism is proposed that supports our experimental observations. Regarding the atmospheric implications, our results suggest that the NO2 degradation on volcanic particles and the corresponding formation of HONO is expected to be significant during volcanic dust storms or after a volcanic eruption.
Keywords: kyselina dusitá; Nitrogen Dioxide; sluneční záření; Atmosphere; Nitrous Acid; prach; Sunlight; Dust; atmosféra; oxid dusičitý